2021
DOI: 10.2174/2666796701999200915145332
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Positive Role of a Higher Education Institution in the Prevention of Misinformation During Pandemics: The Health Committee Model During COVID-19

Abstract: : In Lebanon, with COVID-19 cases escalating and national efforts exhausted in the containment of the pandemic, calls were made for increased awareness, scientific literacy, and the debunking of false information. This article sheds the light on the positive role that a private University can play in spreading scientifically-authenticated, health-related, awareness through the community. The Lebanese International University (LIU) has 9 campuses distributed across all Lebanese Governorates with an extensive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Additionally, press conferences were held to issue important notices and communicate the pandemic changes on a national level. After reevaluating the situation, the government extended the initial lockdown on April 9th for two additional weeks, extended again repeatedly until the end of May 2020; a status of uncertainty and interrupted lockdowns persisted thereafter for almost one year within the pandemic [ 19 ]. As of July 2022, the cumulative number of COVID-19 cases in Lebanon exceeds 1 million, and the disease has claimed the lives of over 10,500 individuals, while vaccination rates are close to 26% [ 20 ].The aforementioned lockdown of course extended to universities as well, and our university rapidly shifted to an online mode of education, which has continued since the spring semester of the academic year 2019–2020 to the present day [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, press conferences were held to issue important notices and communicate the pandemic changes on a national level. After reevaluating the situation, the government extended the initial lockdown on April 9th for two additional weeks, extended again repeatedly until the end of May 2020; a status of uncertainty and interrupted lockdowns persisted thereafter for almost one year within the pandemic [ 19 ]. As of July 2022, the cumulative number of COVID-19 cases in Lebanon exceeds 1 million, and the disease has claimed the lives of over 10,500 individuals, while vaccination rates are close to 26% [ 20 ].The aforementioned lockdown of course extended to universities as well, and our university rapidly shifted to an online mode of education, which has continued since the spring semester of the academic year 2019–2020 to the present day [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since December 2019, the outbreak caused by the severe acute respiratory distress syndrome coronavirus 2 (SARS-CoV-2) has spread to different parts of the world, causing an emerging respiratory illness with serious complications [1]. Soon thereafter, the associated disease, termed coronavirus disease 2019 (COVID- 19), was labeled as a pandemic by the World Health Organization (WHO) [2]. The pandemic continues to affect the lives of hundreds of millions of patients and to have profound effects on society, the environment, the economy, politics, and global biosafety as a whole [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Another factor that may explain the higher influenza vaccination rate in the 2021-2022 study may be the ability of the COVID-19 pandemic to renew awareness of respiratory infections, primarily influenza, an observation highly probable and widely reported in the literature [25][26][27][28], with popuar perceptions of the influenza vaccine during COVID-19 pandemic having positive impact on the influenza vaccine [29]. Specifically, the university health committee, established early during COVID-19, may have exercised a specific influence on university students by extensive awareness campaigns on COVID-19 [30], but this remains inconclusive and cannot be directly assessed using our results. In Lebanon, Youssef et al reported that influenza vaccine intake in the 2021-2022 season was higher than the previous season among healthcare workers [31], a finding consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…This study was a cross-sectional study conducted among students of the Lebanese International University, which has nine campuses distributed over the eight Lebanese governorates, and a student population of about 35,000 students [ 57 ]. The study was conducted using an electronic survey via Google Forms and sent to all enrolled students who were registered in the fall semester during the academic year 2022–2023 via their institutional email.…”
Section: Methodsmentioning
confidence: 99%